Predictive Factors of Maternal Hypothermia During Cesarean Delivery: A Prospective Cohort Study. Issue 2 (June 2018) - Desgranges, F.P.; Bapteste, L.; Riffard, C.; Pop, M.; Cogniat, B.; Gagey, A.C.; Boucher, P.; Bonnard, C.; Paturel, B.; Mullet, C.; Chassard, D.; Bouvet, L.
Abstract : ( Can J Anaesth . 2017;64(9):919–927) Active warming techniques can lessen the incidence of perioperative maternal hypothermia during cesarean delivery (CD), preventing adverse events like wound infection or intraoperative blood loss. Despite wide availability, however, these active warming devices are used in fewer than 20% of units performing CD. Several preoperative and/or intraoperative factors may contribute to maternal hypothermia. This study aims to identify those predictors in order to help prevent maternal hypothermia during CD.